Correlation between Doppler, Manual Morphometry, and Histopathology Based Morphometry of Radial Artery as a Conduit in Coronary Artery Bypass Grafting - Om Prakash Yadava; Vinod Sharma; Arvind Prakash; Vikas Ahlawat; Anirban Kundu; Bikram K. Mohanty; Rekha Mishra; Amit K. Dinda (Cardiology Research and Practice)
Background. Long-term graft patency is the major factor impacting survival after coronary artery bypass grafting. Arteries are superior in this regard. Radial artery is considered the second best conduit after internal mammary artery. Several studies have shown excellent radial artery patency. We evaluated the morphologic characteristics of radial artery by three modalities, (i) preoperative Doppler ultrasound, (ii) intraoperative manual morphometry, and (iii) postoperative histology-based morphometry, and compared these with the aim of validating Doppler as a noninvasive test of choice for preoperative assessment of radial artery. Methods. This was a prospective study involving 100 patients undergoing coronary artery bypass grafting in which radial artery was used. The radial artery was assessed using preoperative Doppler ultrasound studies, intraoperative morphometry, and postoperative histopathology and morphometry. The morphometric measurements included (i) luminal diameter, (ii) intimal and medial thickness, and (iii) intima-media thickness ratio. Results. Using Bland-Altman plots, there was a 95% limit of agreement between the preoperative Doppler measurements and the postoperative histopathology and morphometry. Conclusion. Doppler ultrasound is an accurate screening test for evaluation of radial artery, in terms of intimal/medial thickness and luminal diameter as a conduit in coronary artery bypass grafting and has been validated by both morphometric and histopathology based studies.